Molecular Epidemiology and Clinical Features of Enteroviruses-Associated Hand, Foot, and Mouth Disease and Herpangina Outbreak in Zunyi, China, 2019 - Ai, Yuanhang; Zhang, Weiwei; Wu, Jie; Zhang, Jingzhi; Shen, Meijing; Yao, Shifei; Deng, Chengmin; Li, Xiaoqian; Wu, Dejing; Tian, Peng; Cheng, Xiaoju; Zha, He; et al. (Frontiers in Medicine, 2021)
Background: Hand, foot and mouth disease (HFMD) and herpangina (HA), two of the most common childhood infectious diseases, are associated with enteroviruses (EVs) infection. The aim of this study was to identify the molecular epidemiology of enterovirus causing HFMD/HA in Zunyi, China, during 2019, and to describe the clinical features of the cases. Methods: We collected the information on demographic and clinical characteristics, laboratory data of laboratory-confirmed EVs associated HFMD/HA cases in Zunyi Medical University Third Affiliated Hospital between March 1 and July 31, 2019. EV types were determined by either one-step real time RT-PCR or partial VP1 gene sequencing and sequence alignment. Phylogenetic analysis of CVA6, CVA2, and CVA5 were established based on the partial VP1 gene sequences by neighbor-joining method. Differences in clinical characteristics and laboratory results of the cases were compared among patients infected with the most prevalent EV types. Results: From 1 March to 31 July 2019, 1,377 EVs associated HFMD/HA inpatients were confirmed. Of them, 4 (0.3%, 4/1,377) were EV-A71-associated cases, 84 (6.1%, 84/1,377) were CVA16-associated cases, and 1,289 (93.6%, 1,289/1,377) were non-EV-A71/CVA16-associated cases. Of the randomly selected 372 non-EV-A71/CVA16 cases, EV types have been successfully determined in 273 cases including 166 HFMD and 107 HA cases. For HFMD cases, the three most common types were CVA6 (80.7%, 134/166), CVA2 (5.4%, 9/166) and CVA5 (3.0%, 5/166); similarly, for HA cases, the three most prevalent serotypes were CVA6 (36.5%, 39/107), CVA2 (21.5%, 23/107) and CVA5 (18.7%, 20/107). Phylogenetic analysis showed that subclade D of CVA5, and subclade E of CVA6 and CVA2 were predominant in Zunyi during the outbreak in 2019. Compared with the cases caused by CVA16, the incidence of high fever and severe infection associated with CVA2, CVA5, and CVA6 was higher. Conclusions: The recent HFMD/HA outbreak in Zunyi is due to a larger incidence of CVA6, CVA2, and CVA5. Novel diagnostic reagents and vaccines against these types would be important to monitor and control EV infections.